The variation of functional connectivity and activity before and after thalamotomy surgery (review) - Nili, Mohammad-Hossein H. K.; Esfahan, Shahrzad M.; Bagheri, Yamin; Vahabie, Abdol-Hossein; Sanayei, Mehdi; Ertiaei, Abolhassan; Shirani, Mohammad; Dehaqani, Mohammad-Reza A.; Rezayat, Ehsan (Frontiers in Human Neuroscience, 2023)
Ablation surgeries are utilized to treat certain brain disorders. Recently, these surgeries have become more prevalent using techniques such as magnetic resonance-guided focused ultrasound (MRgFUS) ablation and Gamma knife thalamotomy (GKT). However, as the thalamus plays a critical role in cognitive functions, the potential impact of these surgeries on functional connectivity and cognition is a matter of concern. Various approaches have been developed to locate the ablation target and also investigate changes in functional connectivity before and after surgery. Functional magnetic resonance imaging (fMRI) and electroencephalogram (EEG) are widely used methods for assessing changes in functional connectivity and activity in clinical research. This Review summarizes the use of fMRI and EEG in thalamotomy surgeries. Our analysis shows that thalamotomy surgery can result in changes in functional connectivity in motor-related, visuomotor, and default-mode networks, as detected by fMRI. EEG data also indicate a reduction in over-activities observed in the preoperative state.